On the border of two worlds – the MIGRASSI project (In situ, 2024)
Two necropolises separated by a wall - Crkvina and Maksanova gomila are located at the westernmost corner of Lake Vrana, about fifty meters from its shore. In what way were the people buried in them different during their lifetime so that they could not find their final repose in the same place? The answer to that question lies at the heart of the project and research discussed in the paper.
Keywords: Lake Vrana; Pakoštane; Crkvina; Maksanova gomila; Migrassi